Pengaruh Layanan Aplikasi Go-Food Terhadap Peningkatan Pada UMKM Kuliner Di Jatinangor - Cindy Agustri Rahayu Sitompul (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
In an era marked by rapid technological advancements, numerous culinary businesses have embraced online sales processes to reach a wider customer base. This study aims to investigate the impact of the Go-food application service on the sales performance of Micro, Small, and Medium Enterprises (UMKM) in the culinary sector in Bandung. Leveraging the convenience and accessibility offered by the Go-food platform, this research explores how UMKM businesses have experienced growth in their sales revenue. Through a comprehensive analysis of data collected from participating businesses and customer feedback, the study sheds light on the transformative impact of digital platforms on the culinary industry in Bandung. The results of this study demonstrate the positive influence of the Go-food service on increasing sales for UMKM culinary businesses in Bandung.